2017
DOI: 10.1111/phpp.12355
|View full text |Cite
|
Sign up to set email alerts
|

Unique profile of antimicrobial peptide expression in polymorphic light eruption lesions compared to healthy skin, atopic dermatitis, and psoriasis

Abstract: SummaryBackgroundPolymorphic light eruption (PLE) has been attributed to type IV, most likely delayed‐type hypersensitivity response (adaptive immunity) but little is known on innate immunity, especially antimicrobial peptides (AMPs) in the disease. Abnormalities in AMP expression have been linked to pathological skin conditions such as atopic dermatitis (AD) and psoriasis.MethodsAntimicrobial peptide profiling was carried out in PLE skin samples (n,12) compared with that of healthy (n,13), atopic (n,6), and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…Similar to photosensitive rosacea, in which LL‐37 increases UVB‐triggered inflammasome activation, this AMP may also play a role in PLE‐koebnerized psoriasis as we found it to be significantly increased in blood vessels in the dermis of lesional PLE skin compared to healthy skin (Fig. c) . This is consistent with the observation that LL‐37 expression is commonly increased in psoriasis and other inflammatory diseases such as lupus erythematosus and contact dermatitis, but downregulated in atopic dermatitis .…”
Section: Initiators Of Photosensitive Psoriasissupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to photosensitive rosacea, in which LL‐37 increases UVB‐triggered inflammasome activation, this AMP may also play a role in PLE‐koebnerized psoriasis as we found it to be significantly increased in blood vessels in the dermis of lesional PLE skin compared to healthy skin (Fig. c) . This is consistent with the observation that LL‐37 expression is commonly increased in psoriasis and other inflammatory diseases such as lupus erythematosus and contact dermatitis, but downregulated in atopic dermatitis .…”
Section: Initiators Of Photosensitive Psoriasissupporting
confidence: 89%
“…TLRs can also regulate AMP expression, and laboratory studies have shown that exposure to UV can induce the AMPs human beta‐defensin (HBD) 2, HBD3, RNAse7 and S100A7 (psoriasin) by keratinocytes in vitro and in vivo . Intriguingly, exposure to UV can lead to upregulation of AMP in an atypical manner in patients with PLE when compared to healthy subjects . Importantly, topical treatment with vitamin D3 analogues such as calcipotriol, known to suppress cellular immune response through expansion of Tregs, has been found to decrease the expression of AMPs including HBD2 and psoriasin in psoriatic skin (cited in Ref.…”
Section: Initiators Of Photosensitive Psoriasismentioning
confidence: 99%
“…Patra et al have found that the expression of psoriasin, RNase7, HBD-2, and LL-37 was increased in PLE lesional skin, whereas HBD-3 was decreased. Considering the skin surface as a “multiethnic world,” without forgetting the crucial role of keratinocytes, we can't exclude that AMPs release could be determined by modification in microbiome components after UV interaction ( 23 ). Indeed, microbiome could represent the source, direct or indirect, of the yet undetected UVR-induced antigens formed in PLE patients, leading to keratinocyte damage.…”
Section: Pathophisiology Of Polymorphic Light Eruption: What's New?mentioning
confidence: 99%
“…Indeed, microbiome could represent the source, direct or indirect, of the yet undetected UVR-induced antigens formed in PLE patients, leading to keratinocyte damage. As a consequence, LL-37, also induced by UVB, IFNγ, TNF-α, IL-6, could represent a potential indirect driver of PLE ( 23 ). It can form aggregates with self-nucleic acids able to activate pDCs: in psoriasis it has been recognized as the main autoantigen ( 24 ).…”
Section: Pathophisiology Of Polymorphic Light Eruption: What's New?mentioning
confidence: 99%
“…Might a nerve scar left behind after successful treatment contribute to the reappearance of psoriatic lesions, be it during or after continuous treatment? Last but not the least, may the interplay of the microbiome and AMPs [85,86] help trigger psoriatic recurrence? This may be in particular important for pustular psoriasis, in which IL-1/IL-36 plays an important role in the pathogenesis [87][88][89].…”
Section: Conclusion and Open Questionsmentioning
confidence: 99%